2021
DOI: 10.1038/s41598-021-03233-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns in the sex ratio of American lobsters (Homarus americanus) in southwestern Nova Scotia, Canada

Abstract: An approximate 1:1 sex ratio of American lobsters can be skewed due to environmental factors or fisheries management. Substantial skewness can impact mating behaviour and lower reproduction which could have far-reaching ecological and economic consequences. The aim was to investigate the sex ratio patterns of lobsters in two lobster fishing areas (LFAs) in southwestern Nova Scotia, Canada and identify factors associated with skewed sex ratios. This study analyzed biological data from more than 270,000 lobsters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Only one bacterial taxon had a significantly different abundance between male, female and berried female lobsters. Observing no significant differences in the alpha and beta diversity of the shell microbiome between lobster sex and size was somewhat surprising, as berried females and larger lobsters molt less often and have different preferred habitats ( Cobb, 1976 ; Castro and Somers, 2012 ; Koepper et al, 2021 ). A longer time in their shell could imply a distinct microbial community as bacterial taxa, including pathogenic taxa, have more time to proliferate and colonize the carapace, but this was not observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Only one bacterial taxon had a significantly different abundance between male, female and berried female lobsters. Observing no significant differences in the alpha and beta diversity of the shell microbiome between lobster sex and size was somewhat surprising, as berried females and larger lobsters molt less often and have different preferred habitats ( Cobb, 1976 ; Castro and Somers, 2012 ; Koepper et al, 2021 ). A longer time in their shell could imply a distinct microbial community as bacterial taxa, including pathogenic taxa, have more time to proliferate and colonize the carapace, but this was not observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Sex ratio can also be affected by localized environmental factors, such as temperature, since mature females tend to favor cooler, deeper waters than males at certain times of the year (Crossin et al 1998; Cowan et al 2007). Koepper et al (2021) found that a combination of fishing pressure and environmental factors affect sex ratios in Nova Scotia waters, with female‐skewed sex ratios occurring in areas of high fishing effort and cooler, deeper waters. It is possible, therefore, that future reductions of fishing effort in the Monument will modify sex ratios, presumably towards a lower proportion of females if male‐biased fishing mortality is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Sex ratio varies widely across the American lobster species' range (ASMFC 2020; Koepper et al 2021). It is influenced by harvesting pressure since males generally incur higher fishing mortality than females, which can ultimately lead to sperm limitation if populations become heavily female biased (MacDiarmid and Butler 1999; Pardo et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical data on capture productions of Charybdis species in the China Fishery Statistical Yearbooks are the only resource nation contributing to FAO fishery statistics and have been available since 2003. A declining trend in capture productions of Charybdis species has been noticed from approximately 12% (~72,000 t) of the annual total swimming crab production in 2003 to <4% (~22,000 t) in 2020 (MOA, 2003-2017, MARA, 2018-2021. However, studies from reproductive biology and population structure to fishery patterns on Charybdis species are limited, irrespective of their commercial importance in crustacean fisheries.…”
Section: Introductionmentioning
confidence: 99%